Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

According to my sheet of standard integrals,

$\int \csc^2x \, dx = -\cot x + C$.

I am interested in a proof for the integral of $\operatorname{cosec}^2x$ that does not require differentiating $\cot x$. (I already know how to prove it using differentiation, but am interested in how one would calculate it without differentiation.)

share|cite|improve this question
If you know how to differentiate the cotangent, then you know how to integrate the result of differentiating the cotangent... – J. M. Nov 18 '12 at 13:28
You can differentiate -cot x+C – Amr Nov 18 '12 at 13:28
I agree with @J.M.: this belongs to any table of elementary primitives that you should learn by heart. – Siminore Nov 18 '12 at 13:29
Taking the derivative of $\cot$ is trivial though. It's by definition $1\over\tan$, so you just use the quotient rule. And then use that $\csc = {1\over\sin}$ (again by definition). (You silly Americans and your need to have separate names even for the reciprocals of the trigonometric functions :D) – kahen Nov 18 '12 at 13:33
Alright, if a (Weierstrass-like) substitution is good enough for you: let $x=\arctan\,u$... – J. M. Nov 18 '12 at 13:43
up vote 3 down vote accepted

If you want to be that perverse. I learned a way to integrate a power of sine, so why not apply it to the $-2$ power? Keep one factor of sine, convert all others to cosine, substitute $u=\cos x$. If we do that here, we get $$ \int\frac{dx}{\sin^2 x} = \int \frac{\sin x dx}{\sin^3 x} =\int\frac{\sin x dx}{(1-\cos^2 x)^{3/2}} =\int\frac{-du}{(1-u^2)^{3/2}} . $$ Then we can evaluate this integral (somehow, maybe even a trig substitution) to get $$ \int\frac{-du}{(1-u^2)^{3/2}} = \frac{-u}{\sqrt{1-u^2}} + C = \frac{- \cos x}{\sin x} + C $$

share|cite|improve this answer
That was genius. I knew how to integrate powers of sine, but I didn't think to apply it here. Thanks. (When I get enough reputation I will upvote this.) – daviewales Nov 19 '12 at 2:38

Alright, we could attempt a Weierstrass substitution if that's the sort of thing you want. Let $t=\tan(\frac{x}{2})$. Thus $\csc(x)=\frac{1+t^{2}}{2t}$ and $dx=\frac{2dt}{1+t^{2}}$. Therefore we have the following:
$$\int \csc^{2}(x)dx=\int \frac{1+t^{2}}{2t}\cdot\frac{1+t^{2}}{2t}\cdot\frac{2dt}{1+t^{2}}=\int\frac{1+t^{2}}{2t^{2}}dt=\frac{1}{2}\int (t^{-2}+1) dt$$ $$=\frac{1}{2} \left[ \frac{-1}{t}+t\right]+C=\frac{t^{2}-1}{2t}+C=\frac{\tan^{2}(x/2)-1}{2\tan(x/2)}+C$$
Which leads to the given result by application of the double angle formula.

Letting $u=\tan(x)$ works too. We get $\csc^{2}(x)=1+\frac{1}{u^{2}}=\frac{1+u^{2}}{u^{2}}$, and $\frac{du}{1+u^{2}}=dx$. Therefore the integral is $$\int \csc^{2}(x)=\int \frac{1+u^{-2}}{1+u^{2}}du=\int \frac{1}{u^{2}}du=\frac{-1}{\tan(x)}+C=-\cot(x)+C$$

share|cite|improve this answer
Things are quite simpler if you let $t=\tan\,x$... – J. M. Nov 18 '12 at 23:49
I would upvote this if I had enough reputation. Thanks. – daviewales Nov 19 '12 at 2:25
@J.M. Thanks, I've added this in. – Daniel Littlewood Nov 19 '12 at 18:18
Okay, upvoted. :) @davie: you should now have sufficient rep for voting... – J. M. Nov 19 '12 at 22:47
Thanks @J.M. =D – daviewales Nov 20 '12 at 10:45

Use the trig identity for $\text{csc}^2x$ and write the expression in terms of $\text{sin }x$ and $\text{cos }x$: $$ \int{\text{csc}^2x\text{ }dx}=\int{(\text{cot}^2x+1)\text{ }dx}=\int{\text{cot}^2x\text{ }dx}+\int{dx}=\int{\frac{\text{cos}^2x}{\text{sin}^2x}\text{ }dx}+\int{dx} $$ Prepare for integration by parts: $$ u=\text{cos }x~~~~~~~~~~du=-\text{ sin }x\text{ }dx~~~~~~~~~~dv=\frac{\text{cos }x}{\text{sin}^2x}\text{ }dx~~~~~~~~~~v=-\frac{1}{\text{sin }x} $$ Integrate by parts and simplify: $$ \int{\frac{\text{cos}^2x}{\text{sin}^2x}\text{ }dx}+\int{dx}=-\frac{\text{cos }x}{\text{sin }x}-\int{\frac{-\text{ sin }x}{-\text{ sin }x}\text{ }dx}+\int{dx}=-\text{ cot }x+C $$

share|cite|improve this answer

Question: $\displaystyle\int{\csc^2(x)dx} = $

Using substitution: $u = \dfrac{1}{\sin^2(x)}$

$\dfrac{du}{dx} = \dfrac{-2\cos(x)}{\sin^3(x)} \quad \longrightarrow du = \left(\dfrac{-2\cos(x)}{\sin(x)}\right)\times \left(\dfrac{1}{\sin^2(x)}\right)dx$

$\therefore -\dfrac{1}{2}\tan(x)du = \dfrac{1}{\sin^2(x)} dx \qquad (1)$

We still must find what is $\tan(x)$ in terms of $u$, hence:

$u = \dfrac{\sin^2(x) + \cos^2(x)}{\sin^2(x)} = 1+ \cot^2(x)$

$u-1 = \cot^2(x)$

$\sqrt{u-1} = \cot(x)$

$\dfrac{1}{\sqrt{u-1}} = \tan(x)$

Therefore substitute in $(1)$ and our integral becomes:

$-\dfrac{1}{2}\displaystyle\int{(u-1)^{-\frac{1}{2}}}du = -\dfrac{1}{2}\dfrac{\sqrt{(u-1)}}{\dfrac{1}{2}} + C = -\sqrt{\left(\dfrac{1}{\sin^2(x)} - 1)\right)} + C $

$= -\sqrt{\left(\dfrac{1-\sin^2(x)}{\sin^2(x)}\right)} + C = -\cot(x) + C$

Hope this makes sense,

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.